Water scarcity in Chennai, India: Institutions, entitlements and aspects of inequality in access - P. B. Anand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The main contributions of the paper can be divided into five areas. (a) It tries to explain conceptually, the institutional arrangements for water supply in Chennai and whether the state government's decision about improving the performance of the water utility depends on particular political circumstances. A plausible explanation is also given of the impact of ground water regulation on the supply decision of private sector (tanker truck operators), using a crowding out framework. (b) It discusses how Amartya Sen's entitlements approach could be used to understand water scarcity as a problem of some people not having enough water rather than a problem of there being not enough water, and in that light, to examine inequality in access to water supply. (c) The paper presents a water balance sheet for Chennai. While I do not use a computable general equilibrium (CGE) model, I suggest a possible framework to use such models for water supply policy issues at city level. (d) Aspects of water quality are discussed by focusing on the steps taken by households to improve water quality at home, and whether access to energy also contributes to entitlement deprivation of the poor. (e) Monthly household expenditure on water supply is briefly examined. These expenditures comprise direct costs, the cost of time spent in collecting water, and expenditure incurred in improving the quality. Expenditure on water is found to be positively associated with years of education of the respondent, water endowment, home ownership and location within Chennai City (as compared to residing in the peri-urban areas). The low income households do spend a slightly larger proportion of their monthly income on water supply as compared to others, mainly in the form of the cost of time spent in collecting water. Due to energy prices and lack of access to certain sources of energy, they may also be suffering from entitlement deprivation in having to settle for using water of low quality and increased health risk. – utilities ; water supply ; entitlements ; regulation ; Asia
Keywords: D63; H42; H7; L51; L95; Q25; 330